Gut microbial profiles of patients with optic neuritis or myasthenia gravis - Tao Wu; Hanqiu Jiang; Chen Lin; Jingting Peng; Xiuyun Kong; Jie Yu; Jiawei Wang; Shilei Cui (Journal of International Medical Research)
Objective To characterize the gut microbial composition of patients with optic neuritis (ON) or myasthenia gravis (MG). Methods Stool samples were collected from 45 patients with ON, 13 patients with MG, and 20 healthy controls. Microbial genomic DNA was extracted, and the V3–V4 regions of bacterial 16S rRNA genes were amplified and sequenced. Bioinformatic analyses was performed to compare the alpha-diversity, beta-diversity, taxonomic assignments, and bacterial richness of the groups. Differences in the abundances of microbial taxa were identified using linear discriminant analysis effect size (LEfSe) and analysis of variance. Results Beta-diversity analysis showed distinct clustering of patient samples from the healthy controls. At the phylum and genus levels, Actinobacteria , Bacteroidetes , Firmicutes , and Proteobacteria predominated, but their proportions varied between groups. LEfSe analysis identified microbial taxa that were associated with each group. The patients showed lower abundances of certain intestinal probiotics, including Bifidobacterium , Bacteroides , and Roseburia , than the controls. No significant differences were found between the disease subgroups. The Carnobacteriaceae family was significantly less abundant in the ON than in the MG group. Conclusion We have identified significant alterations in the gut microbiota of patients with ON or MG, and importantly, a notable reduction in intestinal probiotics.